2012
DOI: 10.1097/phm.0b013e318228c505
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Quadriceps Strengthening on Pain, Function, and Patellofemoral Joint Contact Area in Persons with Patellofemoral Pain

Abstract: Weight-training exercise increased knee muscle strength and the patellofemoral joint contact area, which could reduce mechanical stress in the joint, improving pain and function in subjects with PFPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 31 publications
2
45
0
5
Order By: Relevance
“…Kujala skalası; hastalığa spesifik, yaygın olarak kullanılan, geçerli, güvenilir ve duyarlı bir değerlendirme ölçeğidir. Ön diz ağrısını değerlendirmek üzere tanımlanan sonuç ölçütlerinin geçerliliği ve güvenilirliği ile yapılan çalışmalarda, Kujala ön diz ağrısı skorunda meydana gelen %10 değişikliğin iyileşmeyi temsil ettiği gösterilmiştir (1,20,21). Çalışmamızda iyileşmeyi gösteren %10 ve üzeri değişiklik açısından İEG ve EEG arasında fark olmamakla birlikte, her iki grupta da fonksiyonel durumda egzersiz öncesine göre anlamlı düzelmeler saptandı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Kujala skalası; hastalığa spesifik, yaygın olarak kullanılan, geçerli, güvenilir ve duyarlı bir değerlendirme ölçeğidir. Ön diz ağrısını değerlendirmek üzere tanımlanan sonuç ölçütlerinin geçerliliği ve güvenilirliği ile yapılan çalışmalarda, Kujala ön diz ağrısı skorunda meydana gelen %10 değişikliğin iyileşmeyi temsil ettiği gösterilmiştir (1,20,21). Çalışmamızda iyileşmeyi gösteren %10 ve üzeri değişiklik açısından İEG ve EEG arasında fark olmamakla birlikte, her iki grupta da fonksiyonel durumda egzersiz öncesine göre anlamlı düzelmeler saptandı.…”
Section: Discussionunclassified
“…Randomize kontrollü olarak yapılan çeşitli çalışmalar egzersiz bazlı tedavilerin ağrı ve fonksiyon üzerinde olumlu etkisini göstermişlerdir (14,15,20,31). Ancak bunlar arasında ev egzersiz programı ile izokinetik egzersizi karşılaştıran bir çalışma bulunmuyordu.…”
Section: S65unclassified
“…Isometric and concentric quadriceps muscle strengths were evaluated by Cybex Norm®. The authors found increased isometric quadriceps strength (pre/post training difference: 22.44±5.61 N) and isokinetic quadriceps strength (pre/post training difference: 9.33 ± 4.61 N) after their exercise program (47).…”
Section: Weight-bearing Versus Non-weight-bearing Exercisesmentioning
confidence: 96%
“…In conclusion, the authors recommended combining treatments as the initial approach to treating patellofemoral pain but further individualized more functional, global treatment is essential (46). Chiu et al investigated effect of weight training on hip and knee muscle strength in patients with patellofemoral pain syndrome (47). Weight bearing quadriceps extension exercises were performed using a weight machine and a leg-press machine for a leg-press exercise.…”
Section: Weight-bearing Versus Non-weight-bearing Exercisesmentioning
confidence: 99%
“…8 Three recently published reports pertaining to PFPS treatment illustrate challenges to the development of recommendations for clinical application of research evidence. [9][10][11] Ferber et al 9 investigated the therapeutic benefit of hip-strengthening exercises in patients with PFPS who reported running at least 3 times per week for 30 minutes per session. Dolak et al 10 assessed hip and quadriceps strengthening in female PFPS patients, but physical activity level was not considered.…”
Section: Perspective: Patellofemoral Pain Syndromementioning
confidence: 99%